Eva Hesse - Sussman, Elisabeth; San Francisco Museum of Modern Art, San Francisco; Wiesbaden museum, Wiesbaden; Barger, Michelle; Barrette, Bill; Blank, Sharon; Bryan-Wilson, Julia; Clark, Robin; Fer, Briony; Hesse Charash, Helen; Kramarsky, Werner; Krueger, Jay; et al. (San Francisco : Museum of modern art, 2002)
Eva Hesse, a pivotal figure in the development of postwar international art, created paintings, sculpture, and works on papier that are striking in their enigmatic beauty and tactile sensibility. Although much has been written about Hesse's dramatic life - her childhood flight from Nazi Germany, her struggles to gain acceptance as a young artist in New York, her battle with cancer, and her tragic death in 1970 at the age of thirty-four - her artwork has yet to receive her widespread public attention it deserves. This lavishly illustrated volume provides an in depth examination of Hesse's entire oeuvre, focusing on her innovative working methods and choices of materials as well as on the larger aesthetic and philosophical questions raised by her artistic practice. The book presents and documents over 100 works by Hesse in all media. Essays by a distinguished team of writers deal with themes of mutability and decay in Hesse's art, discuss her little known early career in New York and Germany, explore her innovative use of translucent and pliable materials, and examine the role of drawing and collage in her creative process. In addition, a panel of curators, conservators, and colleagues of Hesse considers the complex issues raised by the aging and degradation of a number of her sculptures over the past three decades. Eva Hesse is published in conjunction with a major exhibition co-organized by Elisabeth Sussman for the San Francisco Museum of Modern Art and Dr. Renate Petzinger for Museum Wiesbaden, Germany.
Eva Hesse, San Francisco Museum of Modern Art, San Francisco, February 2 - May 19, 2002 / Wiesbaden Museum, Wiesbaden, June 15 - October 13, 2002
bibliog. p. 335-336
exhibition history and selected reviews p. 325-333
Engels
boek
Keywords: Hesse, Eva